Effect of growth regulators on 'Brookfield' apple gas diffusion and metabolism under controlled atmosphere storage - Brackmann, Auri; Thewes, Fabio Rodrigo; Anese, Rogerio de Oliveira; Both, Vanderlei (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the effect of growth regulators on gas diffusion and on metabolism of 'Brookfield' apple, and to determine their correlation with quality characteristics of fruit stored in controlled atmosphere. A completely randomized design was used with four replicates. After eight months of storage, the effects of water (control), aminoethoxyvinylglycine (AVG), AVG + ethephon, AVG + naphthaleneacetic acid (NAA), ethephon + NAA, sole NAA, 1‑MCP, ethylene absorption by potassium permanganate (ABS), AVG + ABS, and of AVG + 1‑MCP – applied at different rates and periods – were evaluated on: gas diffusion rate, ethylene production, respiratory rate, internal ethylene concentration, internal CO2 content, mealiness, and intercellular space. Fruit from the control and sole NAA treatments had the highest mealiness occurrence. Growth regulators significantly changed the gaseous diffusion through the pulp of 'Brookfield' apple, mainly in the treatment AVG + ABS, which kept the highest gas diffusion rate. NAA spraying in the field, with or without another growth regulator, increased ripening metabolism by rising ethylene production and respiration rate, and reduced gas diffusion during shelf life. AVG spraying cannot avoid the ethephon effect during the ripening process, and reduces both the internal space and mealiness incidence, but it is not able to induce ethylene production or to increase respiration rates.